(untitled) (Italian Review of Legal History, 2024)
How much notary history can help understanding charters and, vice versa, how much charters can help understanding notary history? This theme has been widely investigated by both legal historians and scholars specialized in the many disciplines aimed at focusing on charter’s history (such as e.g. social class history, charter’s history, paleography and diplomatic history). These lines of research have been analyzed the general topics or the specific territories and historical periods. In spite of the fragmentary documentations, light has been shed on charters and notary history across a large number of social and organizational diversity and across different historical epochs. Regarding the early medieval age, I believe that further indications could be deduced from the chronological order of the Lombard edicts and from the laws of Italic kingdom. These sources prescribed the rules to stipulate legal acts and specified the people responsible for their record and implementation. The examination of such sources also helps us to understand which concerns drove legislators in different historical epochs and which were their main aims: chiefly to guarantee charter legality and effectiveness, avoid as much as possible the arising of legal disputes among parties or facilitate the resolution of such disputes. Only in XIIth century, public trust in notary charters was established according to their status of public officers (as we call them nowadays), but this achievement was the unexpected and unforeseen result of a very slowly path. For centuries, legislators had to contrast the ‘perverse’ behavior of those who had asked the drafting of acts or contracts but changed their mind and did not want fulfill the legal commitments made. From this perspective we can analyze the rulers’ ‘double track’ and the basis of a centuries old path through the creation and standardization of the requirements of the legal acts and the related written documentation. As a legal historian I chose, so to say, to start again and retrace in a chronological perspective the edicts of the Lombard kingdom and the legislation of the kingdom of Italy. I did so by linking the rules according to which legal acts had to be recorded in the charters and the ones defining the activity and expertise of the charters writers. Taking into consideration the sequence of rules and their aims, it is possible to trace an itinerary between issues and contexts to find the recurrence of specific fields of tension among governors, charters recorders and their ‘clients’. Such tensions were produced, in the opinion of the legislators, by one of the major challenges of the ‘living law’, that is the general lack of good faith.